Topics on discrete mathematics and combinatorics - ȚURCAȘ, George Cătălin; BAGDASAR, Ovidiu; ANDRICA, Dorin (2025)
The book presents modern results in discrete mathematics and combinatorics,its purpose being to popularise recent developments in this area, andto encourage further research. Structured in ten chapters, it provides theoreticalresults illustrated by many examples and applications.